A scoping review of the social dimensions in food insecurity and poverty assessments - Tina Bartelmeß; Sarah Jasiok; Elias Kühnel; Juliane Yildiz (Frontiers Media S.A., 2022)
Food poverty is a phenomenon that is currently receiving increasing social attention in both the Global South and the Global North. It is often equated with food insecurity, for which numerous assessment tools and reports exist. However, only limited specific data can be found on food poverty. Starting from a theoretical concept of food poverty, this article examines in a scoping review which dimensions of food poverty are captured by indices and indicators of food insecurity and general poverty assessments. The review focuses particularly on the social dimension of food poverty and points out that it is under-reported and that no adequate assessment tools exist so far. Existing indices and indicators of food insecurity and general poverty assessments are critically reviewed and suggestions for the assessment of social food poverty for policy and practice derived.